Revised Draft Second Five-Year Plan Government of Andhra - Planning Commission (Planning Commission, 1955)
The Andhra State came into existence on 1st October 1953, that is exactly half-way through the First Five-Year Plan. The Plan which the State inherited was not prepared by the Composite State with reference to the specific requirements of Andhra and could not in the very nature of things meet the needs of the new State. The Plan now formulated must therefore serve as the real First Plan for this State. A State which to some extent has missed the full opportunity during the First Plan and the resources of which have not been adequately developed till now, can, under a planned economy, justifiably have a programme of development comparatively bigger in scope than what its internal resources alone would warrant.
Government of Andhra